Rifabutin-loaded floating gellan gum beads: Effect of calcium and polymer concentration on incorporation efficiency and drug release - Verma A.; Pandit J.K. (My University, 2025)
Purpose: To formulate rifabutin-loaded floating gel beads for stomach-specific release. Methods: Rifabutin-loaded floating gellan gum beads were prepared by ionotropic calcium-induced gelation in acidic medium. In-vitro buoyancy and drug release studies were performed using a USP dissolution apparatus type II in 0.01M HCl (ph 2.0) as the dissolution medium. The shape, surface morphology and internal structure of the dried beads were examined by scanning electron microscopy. Fourier Transform infrared spectroscopy (FTIR) was applied to investigate drug-polymer interactions. Results: The beads exhibited excellent buoyancy in simulated gastric fluid (SGF) and remained buoyant for 18 h. Drug incorporation efficiency of the beads ranged from 40 to 60% and was dependent significantly (p < 0.05) on the concentrations of calcium ions and gellan gum. Drug release from the floating bead formulations was rapid, with > 50% of the drug released within 1 h. Increased polymer concentration did not significantly (p < 0.05) retard drug release. Conclusion: Incorporation efficiency and release of rifabutin can be controlled by modulation of the investigated parameters. The developed floating gellan gum beads may be suitable for a potential oral stomach-specific release system to treat stomach infections such as multi-drug resistant Helicobacter pylori infection. © Pharmacotherapy Group.